A societal transformation scenario for staying below 1.5°C - Kai Kuhnhenn; Luís Fílípe Carvalho da Costa; Eva Mahnke; Lisa Schneider; Steffen Lange (Heinrich-Böll-Stiftung, 2020)
To stop climate change, we have to limit global warming to 1.5êC. But can we still achieve this target? And if so, what pathways can society take in transiting towards a climate-just economy? One important yardstick emerging from it was the need for global emissions to reach net-zero by 2050, the Intergovernmental Panel on Climate Change (IPCC) says in his "Special Report on Global Warming to 1.5êC". One important problem with this and other scenarios is that virtually all rely on continued global economic growth. The Heinrich Böll Foundation and the Konzeptwerk Neue Ökonomie realised the importance of broadening the discussion's perspective and considering societal pathways that are currently not included in either the IPCC reports or the public debate. Together with researchers from engineering and the natural and social sciences, Heinrich Böll Foundation and Konzeptwerk Neue Ökonomie developed a "Societal Transformation Scenario" for this publication - a global climate mitigation scenario that explores the climate effects of limiting global production and consumptions and of envisioning a broader societal transformation to accompany these transformations to reach a good life for all.
Keywords: 300